Running with the Red Queen: Host-parasite coevolution selects for biparental sex - Morran, Levi T. (2011)
Most organisms reproduce through outcrossing, even though it comes with significant costs. The Red Queen hypothesis proposes that selection from coevolving pathogens facilitates the persistence of outcrossing in spite of these costs. We utilized experimental coevolution to test the Red Queen hypothesis, and found that coevolution with a bacterial pathogen (Serratia marcescens) resulted in significantly more outcrossing in mixed mating experimental populations of the nematode Caenorhabditis elegans. Furthermore, we found that coevolution with the pathogen rapidly drove obligately selfing populations to extinction, while outcrossing populations persisted through reciprocal coevolution. Thus, consistent with the Red Queen hypothesis, coevolving pathogens can select for biparental sex.